Real Estate and Tax Credits: How Can the Tax Credits be used to Make Affordable Housing More Feasible? - Avdeev, Valeriya; Nassiripour, Sia; Wong, Hannah (Archives of Business Research, 2024)
According to the recent Article: “Separated by Design: How Some of America’s Richest Town’s Fight Affordable Housing,” in southwest Connecticut, the gap between rich and poor is wider than anywhere else in the country.[1] According to the article, due to the denials of zoning variances by the local town boards, the share of housing specifically designated for the low-income residents has decreased since 1990. [1] J. R. Thomas, “Invisible Walls: Separated by Design: How Some of America’s Richest Towns Fight Affordable Housing,” Connecticut Mirror, May 22, 2019.